Evaluación de las diferencias de las monografías de drogas vegetales entre las Farmacopeas Oficiales, como referente para el proyecto de Fitofarmacopea Peruana, CENSI - 2017 - Díaz Paico, Lynda Yoriani (2018)
The objective of this work was to evaluate the differences of the vegetable drug monographs among the Official Pharmacopoeias as referents for the Peruvian Phytopharmacopoeia project, CENSI - 2017. The herbal medicinal products have been a fundamental part in the pharmacopoeias of all cultures of the world. Since 1975, the World Health Organization recognized the importance of traditional medicines, as well as quality control applied to all phases of the development of products based on plant drugs, which allowed the publication of some monographs. According to Law No. 27300, it establishes that the Traditional Medicine Institute (INMETRA), now converted into the Traditional Medicine of Executive Directorate of the Intercultural Health for National Center (CENSI), is in charge of preparing the Herbal Pharmacy of Peru. The Peruvian Phytopharmacopoeia project has 15 monographs on plant drugs, for which official foreign pharmacopoeias were reviewed and analyzed to take them as references, finding differences. Finally, it is concluded that, among the revised pharmacopoeias, the Brazilian Pharmacopoeia and the USP 40 Pharmacopoeia, are better adapted to the American Continent, for their relevance in accessible trials and techniques, in the case of Peru, the entities that use this instrument prefer the USP 40 Each country is required to adopt its rules and regulations to control the production of its herbal products